PLASTISITAS FENOTIP CANGKANG DAN OPERKULUM FAMILI NERITIDAE (GASTROPODA: MOLUSKA) DI MUARA LAMPON SEBAGAI PEREKAM JEJAK POLUTAN MERKURI - Rohmah, Fatimatul; Susintowati; Prasetiyo, Totok Hari (JURNAL BIOSENSE, 2025)
This research aims to prove the ability of phenotypic plasticity of Neritidae members in Lampon Banyuwangi, which is thought to be able to be used to determine the effects of mercury pollution that has been going on for more than a decade. The research method is descriptive quantitative with measurements of shell and operculum morphometry as phenotypic plasticity characters. Phenotypic plasticity analysis used non-Metric Multidimensional Scaling (nMDS) with Past 4.03 software. Based on the results of shell and operculum morphometry and nMDS similarity analysis, there were differences in the shell morphometry of Nerita argus and Nerita costata specimens from the Lampon estuary compared to specimens from the control location, namely Grajagan Beach. Nerita argus specimens from the rocky coast of Lampon had a range of morphometric ratios that were not much different from control specimens. Based on the results of these morphometric measurements, it show that the effects of mercury pollution have a greater influence on the phenotype of the Nerita argus and Nerita costata specimens located in the Lampon estuary compared to the rocky Lampon Beach specimens. The phenotypic plasticity of Nerita argus in the Lampon estuary can be a record of the behavior of mercury affecting marine biota, because the shell and operculum of this Gastropod member are influenced by environmental factors including pollutants, especially during the process of shell formation during its life.